2006
DOI: 10.1111/j.1745-4514.2006.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Herbs to the Accumulation of Histamine in "Otlu" Cheese

Abstract: The aim of this study was to determine the effect of herbs and the use of raw milk on histamine accumulation in “Otlu” (Herby) cheese during ripening. Cow's milk was used for the cheese production. The milk was divided into two main groups: one was used raw and the other was pasteurized at 65C for 30 min. Each group was further divided into two subparts, one of which was used as control (without herbs), while 2% (w/v) of the herbs were added into the other to produce Herby cheese. All cheeses were ripened at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…The determination of B. melitensis from sheep milk samples is important in production of Herby Cheese (Otlu Peynir), one of the popular cheeses traditionally produced from raw milk of sheep, goat and cow or a mixture of these in eastern Turkey, including the Van region (Ekici et al 2006). Thus, Herby Cheese may be a route for transmission of brucellosis to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of B. melitensis from sheep milk samples is important in production of Herby Cheese (Otlu Peynir), one of the popular cheeses traditionally produced from raw milk of sheep, goat and cow or a mixture of these in eastern Turkey, including the Van region (Ekici et al 2006). Thus, Herby Cheese may be a route for transmission of brucellosis to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, brucellosis is one of the major problems of the sheep industry in Turkey, and it could be estimated that the disease results in huge economic losses. Moreover, in the region of Van in East Anatolia in Turkey, humans often consume Herby Cheese (Otlu Peynir) produced from raw milk (Ekici et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Otlu cheese is ripened in brine or in earthenware or plastic containers using dry-salting. In the past, drysalted cheeses were ripened underground; however, at present, this method of salting has been replaced by brining [14,17]. It was reported that the use of different herbs and their level significantly influence the chemistry, biochemistry and sensory characteristics of Otlu cheese.…”
Section: Otlu Cheese (Herby Cheese)mentioning
confidence: 99%
“…Addition of some herbs, such as Allium [10,15], Prangos [41] or Chaerophyllum [45] enhanced proteolysis in Otlu cheese during ripening (Fig. 2).…”
Section: Proteolysismentioning
confidence: 99%
“…When dry-salting is used, the cheese is ripened underground for at least 3 months. However, this traditional production method has been replaced in dairies by brine-salting and marketed vacuum-packed in containers [8,15]. …”
Section: Otlu Cheesementioning
confidence: 99%